Implementasi Pendidikan Entrepreneur di PTKI : Kurikuler, Estrakurikuler dan Sarana - Hosen, Hosen (Al-Abshar: Journal of Islamic Education Management, 2023)
PTKI offers entrepreneurship education. This paper provides a systematic explanation of the importance of PTKI entrepreneurship education. This paper also assumes that PTKI students will begin to recognize and start businesses as a result of entrepreneurship education. In order to prepare students to become independent workers or business owners in the future, entrepreneurship can be taught through inculcating entrepreneurial values. An integrated curriculum developed at the Islamic Religious College (PTKI) that applies principles and methodologies for the development of life skills in students is a feature of entrepreneurship-oriented education. This research is a library research, namely a study in which data collection is carried out by collecting data from various literatures. This research is also an analytic descriptive research, namely trying to present data related to the Implementation of Entrepreneur Education in PTKI This research results that through entrepreneurship education it will prepare PTKI students to be more able to compete in the job market, have quality and expertise, have a strong work ethic, and perform well in the institution where they work, and have new ideas while serving. . They can demonstrate their value in a variety of development endeavors, including development programming, agency management, business operations, and other social endeavors. If PTKI alumni were previously educated as entrepreneurs, they are believed to have higher quality, expertise, and work ethic because they are taught good work habits and management skills, develop self-confidence, and are used to mastering business or work fields